Developing a Behavior Model for Utilitarian Service Consumers toward Engagement in Online Brand Communities - Azadeh Goodarzi; Naser Azad; Mir Ahmad Amirshahi; Asghar Moshabaki Esfahani (‫مدیریت بازرگانی, 2023)
Objective The present study aims to explain the behavioral pattern of utility service consumers toward engagement in online brand communities. Many companies seek to attract and communicate more with customers; therefore, they try to strengthen their relationships with customers by creating online brand communities and customer engagement. Utility companies are affected by this trend in recent years while, compared to hedging companies, they face more challenges in this area. In the extant literature, few studies have investigated the types of behavioral responses of utilitarian service consumers in online brand communities. Therefore, this study seeks to develop a behavioral model for utility service consumers to ensure their engagement. It divides the consumers based on their behavioral differences and by examining each category of them separately in an independent phase.